The Transcription Factor XBP1 in Memory and Cognition: implications in Alzheimer's Disease - Moustapha Cissé; Eric Duplan; Frédéric Checler (BMC, 2017)
Abstract X-box binding protein 1 (XBP1) is a unique basic region leucine zipper transcription factor that was isolated two decades ago in a search for regulators of major histocompatibility complex class II gene expression. XBP1 is a very complex protein that regulates many physiological functions, including the immune system, inflammatory responses and lipid metabolism. Evidence over the past few years suggests that XBP1 also plays an important role in pathological settings, since its activity as a transcription factor has profound effects on the prognosis and progression of diseases such as cancer, neurodegeneration and diabetes. Here we provide an overview of recent advances in our understanding of this multifaceted molecule, particularly in regulating synaptic plasticity and memory function, and the implications in neurodegenerative diseases, with an emphasis on Alzheimer's disease.